Analisis Faktor-Faktor Yang Mempengaruhi Kemampuan Pengembalian Kredit Petani Kelapa Sawit Pada PT. Bank Rakyat Indonesia (Persero) di Kecamatan Air Joman Kabupaten Asahan - Helmina Simanjuntak; Heni Widiya; Henky Japina (CV. ITTC INDONESIA, 2025)
This study aims to analyze the factors that influence the ability to repay credit of oil palm farmers at PT. Bank Rakyat Indonesia (Persero) in Air Joman District, Asahan Regency. This study applies a quantitative approach with an associative research method. oil palm farmers who have credit loans at PT. BRI (Persero) in Air Joman District, Asahan Regency using a research sample of 60 people. Data were obtained through observation, questionnaires, and literature studies. Furthermore, data from the questionnaire were analyzed using multiple linear regression methods. The results of the study obtained based on partial tests (t-tests) showed that each factor of living expenses, other loans, financial management, production costs and credit literacy had a positive and significant effect on the ability to repay credit of oil palm farmers at PT. Bank Rakyat Indonesia (Persero) in Air Joman District, Asahan Regency, based on simultaneous tests (F-tests) it was found that the factors of living expenses, other loans, financial management, production costs and credit literacy had a positive and significant effect on the ability to repay credit of oil palm farmers at PT. Bank Rakyat Indonesia (Persero) in Air Joman District, Asahan Regency.